Influencing factors of short-form video addiction among Chinese university students: a systematic review - Zhan, Xiaoling; Zhu, Weijia (Frontiers in Psychology, 2025)
IntroductionThis systematic review explores the influencing factors of short-form video addiction (SVA) among Chinese university students over the past 5 years. It offers theoretical and practical implications for understanding and preventing SVA among university students and suggests future research directions.MethodsThis review identified 28 eligible peer-reviewed articles from seven English and Chinese databases. The protocol was pre-registered in PROSPERO (CRD420251030636).ResultsThe findings indicate that SVA among university students is prevalent and multifactorial. Influencing factors include eight domains: demographic, psychological, personality traits, behavioral, social, family, motivation for media use, and platform-induced factors.DiscussionGuided by the I-PACE model, the review organized these domains into the person–affect–cognition–execution framework. Personal factors include demographic and personality traits; social and family factors represent persons' external environmental influences; affective and cognitive components comprise psychological factors and media use motivations; and execution factors include behavioral and platform-induced influences. These components interact with each other and collectively predict SVA throughout university students' development. Psychological and personality trait factors often serve as mediating or chained mediating variables for other influencing factors. Conflicting findings regarding demographic, personality, and psychological influences may result from sample homogeneity and research design limitations. Research gaps remain in policy factors and longitudinal or intervention-based studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251030636, PROSPERO: CRD420251030636.